Figure Sculpture in Wax and Plaster - Richard McDermott Miller 1922-2004; Gloria Bley Miller (USA Watson-Guptill Publications, 1975)
"The author describes how to work with wax: modifying waxes, controlling temperature, cooling, heating, cutting, and modeling wax."--Book jacket.
Keywords: Figure sculpture -- Technique; Plaster sculpture; Wax-modeling; General